2015
DOI: 10.5489/cuaj.2439
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent RCC with tuberculous para aortic lymphadenopathy: A pleasant surprise

Abstract: A middle-aged man with end-stage renal disease presented with biopsy-proven left renal cell carcinoma (RCC) and extensive lymphadenopathy on ultrasound/magnetic resonance image. He and his family were counselled on his poor prognosis based on imaging findings, which showed multiple enlarged lymph nodes, appearing metastatic. He underwent laparoscopic radical nephrectomy along with lymph node dissection. Biopsy revealed RCC with all tuberculous lymph nodes. It was a surprise for the patient and treating clinici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Pushkar report showed that UGTB and RCC can have a combined presentation, he reported a middle-aged gentleman who is known to have chronic kidney disease, the patient presented with left renal mass, U/S-guided biopsy and histopathology revealed RCC with multiple enlarged lymph nodes. After nephrectomy and lymph dissection, it turned out to be involved with mycobacterium under the microscope [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pushkar report showed that UGTB and RCC can have a combined presentation, he reported a middle-aged gentleman who is known to have chronic kidney disease, the patient presented with left renal mass, U/S-guided biopsy and histopathology revealed RCC with multiple enlarged lymph nodes. After nephrectomy and lymph dissection, it turned out to be involved with mycobacterium under the microscope [ 9 ].…”
Section: Discussionmentioning
confidence: 99%